Comparison of Efficacy and Side Effects of Multispot Lasers and Conventional Lasers for Diabetic Retinopathy Treatment - Hande Çeliker; Azer Erdağı Bulut; Özlem Şahin (Türk Oftalmoloji Dergisi, 2017)
Panretinal photocoagulation (PRP) is a standard treatment for proliferative diabetic retinopathy. Conventional laser (CL) therapy is performed in one or more sessions in single spot mode. Visual disabilities have been reported after treatment with CL, including central vision loss due to macular edema and peripheral visual field loss resulting from extensive inner retinal scarring. Multispot laser (MSL) photocoagulation has recently been introduced to clinical practice. Studies comparing PRP conducted with MSL and CL have reported that MSLs resulted in less retinal tissue damage and pain, and greater patient comfort compared to CL. The aim of this review was to compare the efficacy and side effects of MSLs and CLs for diabetic retinopathy treatment.